KEMAMPUAN PEMAHAMAN DAN PENALARAN MATEMATIKA SISWA SMA DIKAITKAN DENGAN KEMAMPUAN PENALARAN LOGIK SISWA DAN BEBERAPA UNSUR PROSES BELAJAR-MENGAJAR - Utari Sumarmo, - (1987)
Understanding and mathematics reasoning ability of second grade physics students were tested on 414 senoir high school students. This study evolved from an attempt to determine the relationship among developmental stage or logical reasoning ability of the students, selected aspects of mathemat ics learning-teaching process and understanding and mathematics reasoning ability. In this study , selected aspects of learning-teaching process are restricted to the students' achievement in mathematics, physics, chemistry and in bahasa Indonesia, and also to some students' learning activities and some teaching activities of their teachers.Piaget's theory describes the cognitive structure of an individual which expands with his or her further development- He specifically identifies the cognitive structure of the adolescent as formal operational reasoning. He further characterizes the formal operational child with specific capabilities which have not been possessed by the concrete operational child, these are hypothetico-deductive reasoning, second degree thinking, combinatorial analysis and propositional "reasoning ability. One implication of Piaget's theory in instruction suggests that chidren who do not yet possess the formal operational reasoning should not be taught too abstract materials meaningfully such as